Development of split ring resonator for pineapple moisture content detection - Anis Afrina Mohd Amirudin; Noorsaliza Abdullah; Ezri Mohd (Institute of Advanced Engineering and Science, 2021)
Microwave resonant is one of the sensors used in characterizing the material and is also one of the most sensitive sensors for measuring dielectric properties. This project proposed the resonant method due to its accuracy and sensitivity. The split ring resonators were mounted on the fruit sample surface to observe the resonant frequency behavior, and to measure the fruit freshness. The resonator was set at 6 GHz using the FR4 lossy substrate. The findings show that the coupling distance and the ring radius have the greatest impact on preserving the resonant behavior. The fundamental of the obtained resonant frequencies was observed based on the different moisture content of the test material. The moisture level was observed at 38.2%, 54%, 69%, and 86.7%. At 86.7%, the resonant frequency has the highest shifting by shifting to the left. This shows that the larger resonant frequency change occurs when the water content is higher.